2013
DOI: 10.1007/s00436-013-3465-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular characterization of potentially pathogenic Acanthamoeba genotypes from diverse water resources including household drinking water from Khyber Pakhtunkhwa, Pakistan

Abstract: Acanthamoeba, an opportunistic protozoan pathogen, is ubiquitous in nature, and therefore plays a predatory role and helps control microbial communities in the ecosystem. These Acanthamoeba species are recognized as opportunistic human pathogens that may cause blinding keratitis and rare but fatal granulomatous encephalitis. To date, there is not a single report demonstrating Acanthamoeba isolation and identification from environmental sources in Pakistan, and that is the aim of this study. Acanthamoeba were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…The T4 strains possess properties that provide them more virulent with higher potential for transmission to humans (Maghsood et al 2005b). In addition, the majority of human infections (keratitis, non-keratitis infections such as Acanthamoeba granulomatous encephalitis and cutaneous infections) due to Acanthamoeba have been associated with the T4 genotype (Tanveer et al, 2013). T5 genotype was the second most prevalent genotype of Acanthamoeba in our study which is similar to the result that is owed from recreational areas (Nazar 2011).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The T4 strains possess properties that provide them more virulent with higher potential for transmission to humans (Maghsood et al 2005b). In addition, the majority of human infections (keratitis, non-keratitis infections such as Acanthamoeba granulomatous encephalitis and cutaneous infections) due to Acanthamoeba have been associated with the T4 genotype (Tanveer et al, 2013). T5 genotype was the second most prevalent genotype of Acanthamoeba in our study which is similar to the result that is owed from recreational areas (Nazar 2011).…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, a drug-resistant T5 genotype in a keratitis case has been reported (Iovieno et al 2010). Results clearly make challenge to those categorized T5 as non-pathogenic amoeba (Tanveer et al, 2013). This is the second report of genotype T15 (corresponding to Acanthamoeba jacobsi); after that, it clearly poses the need of further study to identify genotype populations in Iran.…”
Section: Discussionmentioning
confidence: 93%
“…It is noteworthy that in some of samples, Acanthamoeba was also isolated along with Naegleria species from the same water sample (data not shown). In support our group has recently isolated Acanthamoeba species from water resources of Khyber Pakhtunkhwa, Pakistan (Tanveer et al 2015;Tanveer et al 2013). In this regard further studies are necessary to evaluate the properties and quality of water which support amoebae species and Naegleria in particular.…”
Section: Resultsmentioning
confidence: 99%
“…the 1450-bp GTSA.B1 fragment or, preferably, the full sequence of the 18S rRNA gene. So, classification of the strains described by Lanocha et al (2009) requires the use of longer fragments of this gene, as well as the classification of two new genotypes isolated from phylloplane of bromeliad in Brazil (JX683392, Landell et al 2013) and from water in Pakistan (KC203592, Tanveer et al 2013). They were both classified as T16 genotype on the basis of 468-bp and 237-bp fragments, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A new geno-*Corresponding author: boskot@univ.szczecin.pl Malgorzata Adamska et al 434 type, found in bronchoaspirate fluid of a man with chronic marrow leukaemia and bronchoalveolar lavage of newborn with symptoms of atypical pneumonia and named 'T16' (Lanocha et al 2009) may be involved in those clinical symptoms in humans. Since 2010, other authors have described different new strains and described them as 'T16' using the 18S rRNA sequences of various length (Corsaro and Venditti 2010;Landell et al 2013;Tanveer et al 2013). The classification of described until now 'T16' strains is not clear and needs to be rearranged.…”
Section: Introductionmentioning
confidence: 99%